Efektivitas Sediaan Krim dari Ekstrak Daun Dadap Serep (Erythrina subumbrans (Hassk.) Merr.) sebagai Antiinflamasi - I Gusti Agung Ayu Kusuma Wardani; Ni Nyoman Wahyu Udayani; Erna Cahyaningsih; Maria Daniela Tupa Hokor; Ni Made Dharma Shantini Suena (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Inflammation is the mechanism of the body's defense by secreting inflammatory mediators, including bradykinin, prostaglandins, serotonin, and histamine, due to physical or chemical stimuli. Generally, inflammation initiates the body's response to the effect of damaged tissue, for example, in the wound healing process. In Usada Bali, dadap serep leaves were used for wound healing. The design of this study was a randomized control group pretest-posttest design. The anti-inflammatory test of dadap serep leave extract cream used four groups, including KN (negative control), KP (positive control), KF1 (Formula 1 group), and KF2 (Formula 2 group), with a total of 24 rats. Tukey’s analysis showed a significant difference between KN and KP, KF1, and KF2 with significant values (0.031; 0.000; 0.000), respectively. There are significant differences in KP with KF1 and KF2 with significant values (0.050 and 0.021), respectively. In KF1 with KF2, there is no significant difference with the sig value. 0.975. From the research, it can be concluded that the cream of ethanol extract of dadap serep leaves with a concentration of 20% could provide an anti-inflammatory effect in carrageenan-induced rat models.